Cancer stem cells in head and neck cancer: A Mini Review - Silva Galbiatti-Dias, A L; Pavarino, í‰ C; Kawasaki-Oyama, R S; Maniglia, J V; Maniglia, E J V; Goloni Bertollo, E M (Cellular and Molecular Biology, 2015)
Head and neck cancer (HNC) is a multifaceted and genomically complex disease and rapidly emerging preclinical and clinical studies have provided a broader landscape of signaling. It is being realized that intra-tumor heterogeneity, genetic and epigenetic mutations considerably challenge wide ranging therapeutics and patients frequently develop locoregional recurrences, second primary tumours and distant metastases. Using high-throughput technologies, it has been revealed that existence of different subpopulations of cells within tumor mass with different phenotypic and functional properties with distinct tumour-initiating potential is responsible to HNC resistance. In light of accumulating evidence reported in recent years, it is now known that different intracellular proteins and cell surface markers have been used to study CSCs. This review provides an overview of CSC biomarkers in HNC treatment and their potential as therapeutic targets in improving the diagnosis, prognosis and treatment of HNC patients for new therapeutic strategies with information about estimation of prognosis and treatment decision. Further studies regarding biomarkers are necessary to determine the specific role of CSCs in HNC which could be useful in development of new therapeutic strategies to eliminate CSCs and maximize clinical outcome. Furthermore, CD44 still need more research in HNC once the studies show contradictions. Studies using lineage tracing and deep sequencing will provide a comprehensive understanding of CSC model and extent to which it is accountable for resistance against therapeutics and carcinogenesis.